Development and Enhancement of Krajood Basketry Handicraft Using a Combined Heating Krajood Fiber Rolling Machine - Boonchouytan, Worapong; Rawangwong, Surasit; Naemsai, Thanwit; Jareanjit, Jaruwat (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2025)
This study aims to design, construct, and evaluate the performance of a co-heating sedge thread rolling machine to support the development and improvement of sedge weaving handicrafts. The machine has dimensions of 450 mm in width, 850 mm in length, and 700 mm in height. It is powered by a 24 V, 350 W DC motor that drives pulleys connected to a belt, transmitting power to six sets of rollers designed for sedge compression. The rollers have a diameter of 76 mm, and the shafts have a diameter of 25 mm, with a total of 12 rollers. The heating system utilizes a 220 V, 650 W heating rod equipped with a temperature sensor to ensure precise control of the heat level. The experimental parameters included three rotational speeds: 10, 20, and 30 rpm, and three rolling temperatures: 50, 70, and 90 oC. The results demonstrated that the optimal operating conditions were achieved at a rotational speed of 10 rpm and a temperature of 90 oC. Under these conditions, there was no thread breakage, and the desired sedge thread thickness was consistently produced. The machine achieved a production rate of 6.9 kg/hr, which is twice the efficiency of manual labor 3.6 kg/hr. The average sedge thread thickness was measured at 0.31 mm.